Effect of L-Ascorbate on Dexamethasone induced Experimental Insulin Resistance-Role of Oxidative stress. - Biradar, K V (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT In the present study, Vitamin C (L-Ascorbate) was administered (100mg/kg /day) through Diet for Prophylactic as well Therapeutic regimen in Dexamethason (20Âµg/kg /once daily,s.c) Induced Experimental Insulin Resistance in male Wister (240-300g) rats. The animals were grouped into 4 groups 6 in each and estimated Plasma Insulin and Malondialdehy Level in Plasma aswell in Isolated Aortic tissue as a marker of oxidative stress. HOMA-IR index and MASTUDA INDEX were calculated as a marker of an Insulin Resistance and Insulin Sensitivity respectively. From the finding of present study, There was no significant difference in Plasma Insulin level, however significantly reversed (P<0.01) the Increase in plasma triglycerides in vitamin C treated rats when compared with dexamethasone injected rats. Vitamin C significantly prevent and reversed Malondialdehy level in plasma (P<0.01) aswell in Aortic tissue (P<0.05). However, it had no influence on Insulin Resistance and Insulin Sensitivity. In conclusion, Oxidative Stress may not be playing the initiative role in Dexamethasone induced Insulin Resistance.